Rastreamento dos custos ocultos em operações de serviços: estudo de caso em uma sociedade de economia mista com controle estatal na Paraíba - Silva, Paulo César Pereira da (2008)
The development of services economy is no longer a simple question of evidence. The available literature demonstrates this finding, including within the public services itself. The growth of the sector requires adjustments in the structures of organisations, in the behaviour of collaborators and in the systems and procedures. The tracking, identification, assessment and analysis of the costs associated with the services operations, including those of public nature, are inevitable as a necessity to correct organization management. This research investigates the most frequent hidden costs in services in a society of joint economy with state control in the state of Paraiba, from a case study. The evidence of hidden costs in operations services and the lack of methodologies for the assessment are the theoretical framework of this study, thereby; a set of procedures for its implementation was used. The application of the matrix 5Q1C and the use of an adapted framework were fundamental in the elucidation of the problem-issue. The results obtained point to the existence of hidden costs in the process studied, such as: waiting time, useless movement, re-work, absenteeism and idleness. The research concludes that these costs could have been avoided and that the companies lack methodology which promotes the assessment and analysis of these costs. As final recommendations, further suggestion for studies was recommended, focusing on the methodology of procedures for correct identification, tracking, determination and analysis of hidden costs in operations services.